Dispensing Errors Of Unit Dose Drug Distribution System At Central Pharmacy Of Penang Hospital - Elrhman, Gamila Badr A. (2010)

(untitled)
Dispensing error (DE) is the medication error which normally occurred at pharmacy site or service before medications supply or administer to patients. Findings from DE study are used as indicator to determine the quality of the drug supply from drug distribution system of the pharmacy services. DE should be avoided because it may affect patient’s health status complications and prolong hospital stay. Penang Hospital implemented the unit dose drug distribution system in order to reduce medication errors. An observational prospective study was conducted at Central Pharmacy of Penang Hospital for six months to determine data on patients’ demographic characteristics, incidence of DE, pharmacological classes of drugs and types of medications involved and also the risk factors.